APUNTES EPISTEMOLÓGICOS A LA E-CIENCIA. - Vallverdú, Jordi (Revista de Filosofía (00348236), 2008)
Right at the beginning of the 21st century an e-Science is emerging, a highly computerized electronic science which demands a new way of understanding scientific epistemology. Through Bioinformatics and Biotechnologies, the author analyzes some of the characteristics of this new e-Science and shows several problems which contemporary philosophers of science must face.